Słownictwo regionalne – słownictwo gwarowe – słownictwo ludowe - Pelcowa, Halina (Papers in Linguistics, 2019)
The author discusses similarities and differences in the interpretation of words regarded as dialectalisms or regionalisms, collectively named folk vocabulary. She points to several features: assigning values, linguistic awareness of language users, name formation mechanisms, the link between a name and its designator as well as regional and functional scope of words and their place in the lexical inventory of the inhabitants of the countryside, city and region.